Antioxidant potential of different parts of three pineapple varieties N36, Madu and MD2 - Wan Zuraida Wan Mohd Zain (Tanjong Malim, 2023)
Antioxidant potential of different parts of three pineapple varieties N36, Madu and MD2 by Wan Zuraida Wan Mohd Zain